Two case reports of pyoderma gangrenosum and systemic lupus erythematosus: A rare but nonfortuitous association?. Issue 34 (August 2018) - Lebrun, Delphine; Robbins, Ailsa; Hentzien, Maxime; Toquet, Ségolène; Plee, Julie; Durlach, Anne; Bouaziz, Jean-David; Bani-Sadr, Firouzé; Servettaz, Amélie
Abstract: Rationale: Pyoderma gangrenosum (PG), like other neutrophilic dermatosis, may be associated with a variety of systemic disorders including inflammatory bowel diseases, rheumatoid arthritis, and hematologic disorders. Conversely, the association between PG and systemic lupus erythematosus (SLE) has rarely been reported. Patient concerns: We report here 2 cases of this association. Diagnoses: The first case involves a 32-year-old woman who developed, 1 year after SLE diagnosis, 3 painful nodular lesions of PG on her face, and cervical area. The second case was observed in a 37-year-old woman referred for ulcerative nodular papules of PG on her legs, whereas she had been diagnosed with SLE 10 years before. SLE was inactive in the first case, whereas PG occurred during a lupus flare up in the second one. Interventions: We found 23 previous cases of SLE and PG in the literature with most cases (12/20) occurring during a lupus flare. Outcomes: Although rare, this association may be supported by common innate immunity dysregulation and abnormal neutrophil activation. Lessons: PG and other neutrophilic diseases reported in patients with SLE may be added to the large clinical spectrum of cutaneous lesions observed in SLE.